International standard measures during the VaPER bed rest study. (January 2022) - Clément, Gilles R.; Crucian, Brian E.; Downs, Meghan; Krieger, Stephanie; Laurie, Steve S.; Lee, Stuart M.C.; Mulder, Edwin; Roma, Peter G.; Sibonga, Jean D.; Smith, Scott M.; Stenger, Michael B.; Wood, Scott J.; et al.
Abstract: In 2017, the study, Vision Impairment and Intracranial Pressure and Psychological Envihab Research, dubbed VaPER, was conducted in the:envihab facility in Cologne, Germany to determine whether 30 days of bed rest at 6° head down tilt in an increased ambient CO2 (hypercapnic) environment contributes to the deterioration of ocular anatomy and to changes in musculoskeletal, nutritional, hematological, immunological, behavioral, and balance functions. A set of international standard measures were used to evaluate bone, muscle, and nutritional status, and to assess the function of the cardiovascular, sensorimotor, visual, and immune systems, and psychological state. Strict 6° head-down tilt bed rest in an elevated ambient CO2 environment induced mild immunological dysregulation. After bed rest, selenium, urinary iodine, and folate status were lower in the subjects of the VaPER study than they were in subjects of previous bed rest studies of similar duration, which likely reflects regional differences in diet and nutritional status. Bed rest induced optic disc edema in 5 of the 11 subjects. Interestingly, the subjects who were diagnosed with optic disc edema, as determined by fundoscopy imaging, also tended to exhibit higher body temperature and overall higher levels of anxiety and insomnia during bed rest. Highlights: Strict head down tilt bed rest in an elevated ambient CO2 environment induced mild immunological dysregulation. After bed rest, changes in biochemistry reflected regional differences in diet and nutritional status. Subjects who were diagnosed with optic disc edema exhibited higher body temperature and higher levels of anxiety and insomnia during bed rest.